One-Dimensional Convolutional Neural Network with Variable Weights Grey Wolf Optimizer for Modeling of Sand Retention Test - Abd Razak, Nurul Nadhirah (2022)
One-dimensional Convolutional Neural Network (1D-CNN) is a deep learning algorithm that can perform feature extraction, regression, and classification